PROFIL KEMAMPUAN BERPIKIR KREATIF SISWA SEKOLAH MENENGAH PERTAMA DITINJAU DARI TINGKAT KECEMASAN MATEMATIKA DAN JENDER - Wahyuningrum, Endang; Pratiwi, Disti; Adji, Sandra Sukmaning (Jurnal Pendidikan, 2019)
The purpose of this study was to describe the creative thinking skills of junior high school students based on mathematics anxiety and gender. Aspects of creative thinking skills used in this study are fluency, flexibility, and novelty. This research is a qualitative descriptive study. The instruments used were open-ended questions consisting of algebra and geometry questions, mathematics anxiety questionnaires, and interview guidelines. The study was conducted in class IX E of SMPI Al Azhar 12 Rawamangun Jakarta. The subject of this study consisted of four students, they are male student with low mathematics anxiety, female student with low mathematics anxiety, male student with medium mathematics anxiety, and female student with medium mathematics anxiety. The results of the mathematics anxiety questionnaire showed that none of the students in class IX E had high math anxiety. There are differences in the fulfillment of aspects of creative thinking in terms of differences in mathematics anxiety and gender levels. Students with low math anxiety fulfill aspects of fluency, flexibility, and novelty in algebra and geometry questions. Students with medium math anxiety fulfill aspects of fluency and flexibility both in algebra and geometry questions. Female students fulfill aspects of fluency, flexibility, and novelty both in algebra and geometry questions. Male students fulfill aspects of fluency and flexibility in algebra questions, while in geometry questions the aspects that are fulfilled are fluency, flexibility, and novelty.